Lindembergue Cardoso: aspects of a pluralistic musical work (Per Musi, 2012)
In the present article, written just after completing Brazilian composer Lindembergue Cardoso’s catalogue of musical works, the author intends to present the composer’s archive of musical documents, as well as to discuss characteristic aspects of his musical work.  There are 110 works with opus numbers and other pieces without opus number, among which we find arrangements, incidental music, a few transcriptions and orchestrations.